2011
DOI: 10.1186/1742-4690-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of α-helical stapled peptides designed from the HIV-1 capsid dimerization domain

Abstract: BackgroundThe C-terminal domain (CTD) of HIV-1 capsid (CA), like full-length CA, forms dimers in solution and CTD dimerization is a major driving force in Gag assembly and maturation. Mutations of the residues at the CTD dimer interface impair virus assembly and render the virus non-infectious. Therefore, the CTD represents a potential target for designing anti-HIV-1 drugs.ResultsDue to the pivotal role of the dimer interface, we reasoned that peptides from the α-helical region of the dimer interface might be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
54
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 96 publications
2
54
0
Order By: Relevance
“…A peptide mimicking the helix 9 sequence, CAC-1, was shown to inhibit CTD dimerization (21), and a stabilized version of this peptide, NYAD-201, inhibited mature-like virus particle formation (22). These results suggested that targeting CTD dimerization would be a good strategy to identify HIV inhibitors, and we initiated the development of an HTS-TR-FRET assay using the CTD of CA tagged with either GST (GST-CTD) or Flag (CTD-Flag) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A peptide mimicking the helix 9 sequence, CAC-1, was shown to inhibit CTD dimerization (21), and a stabilized version of this peptide, NYAD-201, inhibited mature-like virus particle formation (22). These results suggested that targeting CTD dimerization would be a good strategy to identify HIV inhibitors, and we initiated the development of an HTS-TR-FRET assay using the CTD of CA tagged with either GST (GST-CTD) or Flag (CTD-Flag) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…137 As mentioned above, a Pro-rich loop in the CA NTD binds the peptidyl-prolyl isomerase cyclophilin A. Early studies demonstrated that disruption of the CA-cyclophilin A interaction with cyclosporine inhibited HIV-1 replication.…”
mentioning
confidence: 97%
“…Several molecules that disrupted in vitro CA assembly and virus infectivity resulted from this effort. 136 Debnath and co-workers also designed a dimer interface peptide, NYAD-201, containing the sequence AQEVKXW MTXTLLVA [based on the sequence of CA amino acids [178][179][180][181][182][183][184][185][186][187][188][189][190][191][192], where X represents the (S)-2-(2¢-pentenyl) alanines that are connected by hydrocarbon stapling 137 ]. This stapled peptide penetrates into cells and inhibits HIV-1 production by 3-fold.…”
mentioning
confidence: 99%
“…And second, we have assumed that the peptides dissociate before binding to CTD, but self-associated species could also bind to CTD, as recently shown in stapled peptides. 48 Thus, we can only indicate that the apparent K D values for the peptides designed in this work are smaller than those measured for CAC-1, 15 but we cannot provide a real value of such constants under the approaches used because of the difficulties in measuring the different thermodynamic constants for the concomitant equilibria.…”
Section: Resultsmentioning
confidence: 91%